The Law of Corporate Finance: General Principles and EU Law - Mäntysaari, Petri. author. aut Link
VIII, 426 p.
Keywords: In this three-volume book, the law of corporate finance is defined in a modern way and studied from the perspective of a non-financial firm. The law of corporate finance helps the firm to manage cash flow, risk, principal-agency relationships, and information in the context of all decisions that influence the firm’s finances. The first volume introduces the fundamental concepts and explains the relationship between corporate risk management, the management of agency relationships, corporate governance, and the management of information. The second volume discusses how risk, agency, and information can be managed in all contracts. In addition , the second volume contains an introduction to the legal aspects of payment obligations and the management of various forms of counterparty risk. The third volume discusses a wide range of funding and exit transactions as well as the legal aspects of takeovers.